2016
DOI: 10.1007/s11743-016-1855-2
|View full text |Cite
|
Sign up to set email alerts
|

Rheological Investigation of Wormlike Micelles Based on Gemini Surfactant in EG–Water Solution

Abstract: The self‐assembly behavior of gemini surfactants in ethylene glycol (EG)‐water (5/95, v/v) mixed solvent was investigated by rheological measurements at 10 °C. The influence of molecular structure of the gemini surfactant and added hydrotrope on the solution properties was studied. Sodium salicylate (NaSal) showed stronger ability to induce 2‐hydroxyl‐propanediyl‐α,ω‐bis‐(dimethyldodecylammonium bromide), referred to as 12‐3(OH)‐12, to form wormlike micelles than sodium benzoate. Less NaSal is required to prom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 52 publications
0
3
0
Order By: Relevance
“…This ability to modulate the rheological properties has led to numerous applications for WLMs, including in oil recovery, home-care and personal care products, and as drag-reducing agents. ,, Most studies on WLMs have been conducted in water, and aqueous WLMs have been formed using cationic, , anionic, and zwitterionic surfactants. Reverse WLMs, with their tails facing out towards the solvent, have also been reported in nonpolar liquids (oils). Lastly, some studies have been conducted on WLMs in mixtures of water and polar organic solvents (such as alcohols or diols). To our knowledge, however, there have been no reports of WLMs in pure solvents of intermediate polarity.…”
Section: Introductionmentioning
confidence: 99%
“…This ability to modulate the rheological properties has led to numerous applications for WLMs, including in oil recovery, home-care and personal care products, and as drag-reducing agents. ,, Most studies on WLMs have been conducted in water, and aqueous WLMs have been formed using cationic, , anionic, and zwitterionic surfactants. Reverse WLMs, with their tails facing out towards the solvent, have also been reported in nonpolar liquids (oils). Lastly, some studies have been conducted on WLMs in mixtures of water and polar organic solvents (such as alcohols or diols). To our knowledge, however, there have been no reports of WLMs in pure solvents of intermediate polarity.…”
Section: Introductionmentioning
confidence: 99%
“…This is an indication of a liquid–solid (sol–gel) transition due to electrostatic repulsions, which enhances the stability of the emulsion and may even form a weak crystalline solid (Mewis and Wagner, ). These shear‐induced phenomena also termed as Shear banding (SB) that was observed in a variety of other complex fluids, such as lamellar surfactant phases (Fan et al, ; Salmon et al, ), wormlike micelles (Mei et al, ; Wei et al, ), suspensions (Ragouilliaux et al, ), and polymeric solutions (Kamal et al, ; Ravindranath et al, ). The SB phenomenon is the stratification of the flow into regions of high and low shear rates, trueγ˙, connected by an “interface” of sharp trueγ˙ change in which this homogeneous velocity gradient profile becomes unstable to heterogeneous perturbations and splits into high and low shear rate bands that coexist in the cell, so that the local shear rate varies spatially trueγ˙=trueγ˙()y.…”
Section: Resultsmentioning
confidence: 99%
“…Yang et al () have reported on the effects of surfactant concentration and counterions on the rheological properties of quaternary ammonium Gemini surfactants in high‐performance fracturing fluids. Wei et al () have reported on the rheological properties of cationic Gemini surfactants in ethylene glycol–water solutions. Sodium salicylate was found to promote viscoelasticity to a greater extent than sodium benzoate in self‐thickening deicing fluids.…”
Section: Conflict Of Interestmentioning
confidence: 99%